Facial Authentication As A Bank Security Measure In Zimbabwe - Mashizha, Margaret; Kavhuru, Englon (STIE Indonesia Banking School, 2024)
This paper reports on the findings of a research that was conducted in an endeavour to improve security within the banking sector. The research was triggered by an increase in the number of cyber-attacks on personal bank accounts resulting in the loss of huge sums of money and hence eroding bank confidence among customers. The main objectives of the study were to determine whether customers were aware of facial authentication as a bank security and to assess whether customers would accept facial authentication as a bank security measure. Further, the study was carried out to establish whether it was feasible for banks to implement such a biometric system as part of enhancing bank security and determine the extent to which customers are prone to cyber-attacks. Finally, the research aimed to outline the probable challenges that may be encountered in implementing facial authentication in the banking system. A survey of 70 bank employees and 200 bank customers were selected from two commercial banks using a purposive sampling method. Data was collected using interviews, questionnaires, and an experiment conducted to establish the vulnerability of customers to cyber-attacks. Findings revealed that customers and employees were aware of facial authentication as a measure of bank security and it was a preferred method for bank security in this digital transformation age. Customers were highly prone to attacks as they just clicked links to websites without a second thought. The technology was recommended for the possibility of improving bank security and hence boosting customer confidence and enhancing the security of customer data. However, whilst it was feasible for banks to implement the technology as they have adequate finances, likely challenges to be encountered included a lack of expertise to set up the system and a lack of knowledge on its use amongst customers. The study recommended banks consider facial authentication due to its advantages over other non-biometric methods. The technology is safer especially as it reduces human contact and does not depend on the need for customers to memorise passwords or codes nor does it require them to possess something like smart cards. Keywords: Facial authentication, Password, Bank Security, Personal identification number, customer confidence